Hipersuperfícies estáveis com curvatura média constante e fronteira livre - Santos, Alexandre Jesus dos (2018)
A hypersurface in a manifold, both with nonempty boundary, is called free boundary hypersurface if it is a critical point of the area functional restricted to all admissible variations which preserve volume. A variation is admissible if the boundary and the interior of the manifold contains the boundary and the interior of the hypersurfaces of the variation, respectively. It is well known that free boundary hypersurface has constant mean curvature. In this work we study free boundary hypersurfaces in bounded convex domains in the euclidean space. More precisely, we prove the results obtained by A. Ros and E. Vergasta [18] and I. nunes [15]. As the main result we prove that a stable free boundary surface in the unit ball of the three-dimensional euclidian space has to be either the totally geodesic disc or a spherical cap.